The thermo-elastic vibration of graphene reinforced composite stiffened plate with general boundary conditions. (October 2021) - Maji, Pabitra; Rout, Mrutyunjay; Karmakar, Amit
Abstract: In this numerical study, four different graphene sheets distributions, such as uniformly distributed (UD), functionally graded (FG-X), functionally graded (FG-O), and functionally graded (FG-V), are considered for the free vibration of graphene reinforced composite (GRC) stiffened plate. The graphene is distributed through the thickness of the GRC stiffened plate. The volume fraction of graphene is different in each composite layer except UD cases in which distributions are uniform. The effective material properties of the GRC stiffened plate are obtained based on the Halpin-Tsai approach. An eight-noded isoparametric plate bending element is used to model the present finite element formulation based on first-order shear deformation theory. Three noded isoparametric beam elements with four degrees of freedom per node are used to model the stiffener. In this present investigation, two different X and Y -directional eccentrically at the bottom stiffener is considered. The different parametric studies are also analyzed in this numerical study to determine its consequence on natural frequency. The effect of the number of stiffeners, stiffeners thickness, aspect ratio, thickness ratio, boundary conditions, and temperature on the natural frequency is investigated in detail. The mode shapes of the GRC stiffened plate are also plotted.